Vitamin C Improves Dasatinib Concentrations Under Hypochlorhydric Conditions of the Simulated Stomach Duodenum Model - Moghrabi, Fouad S.; Aburub, Aktham; Fadda, Hala M. (Pharmaceutical research, 2022)
Purpose pH-dependent drug-drug interactions (DDIs) with poorly soluble, weakly basic drugs may lead to clinical implications. Dasatinib is a tyrosine kinase inhibitor with reduced absorption in patients on acid-reducing agents (ARAs). The objective of this study is to investigate the influence of gastric pH on dasatinib supersaturation and determine if vitamin C (L-ascorbic acid) can improve dasatinib concentrations under simulated hypochlorhydric gastric conditions. Methods A dynamic, in vitro , multi-compartment, simulated stomach duodenum (SSD) model mimicking fluid volumes and transfer rates was used to investigate the concentration of BCS class IIb drugs versus time curves. Dasatinib and lamotrigine were explored under normal, fasted, simulated gastric fluids (pH 2) (FaSGF), hypochlorhydric simulated gastric fluids (pH 4.5) (FaSGF hypo ) and FaSGF hypo with 1000 mg of vitamin C. Results Significant supersaturation of dasatinib was observed in the duodenum compartment of the SSD model in FaSGF. A 90% reduction in dasatinib AUC ∞ was observed in FaSGF hypo . Upon addition of vitamin C to FaSGF hypo , drug concentrations were restored to those observed in FaSGF. Lamotrigine AUC ∞ in the duodenal compartment were similar in both FaSGF and FaSGF hypo . The in vitro trends observed for dasatinib and lamotrigine are reflective of the trends observed in vivo in subjects receiving treatment with ARAs. Conclusions The SSD model serves as a good in vitro tool for assessing the effect of pH-dependent DDIs on bioavailability of weakly basic drugs with solubility/ dissolution limited absorption. Vitamin C provides a promising approach for improving bioavailability of poorly soluble, weakly basic drugs in hypochlorhydric patients.